Development and clinical utility analysis of a prostate zonal segmentation model on T2-weighted imaging: a multicenter study - Lili Xu; Gumuyang Zhang; Daming Zhang; Jiahui Zhang; Xiaoxiao Zhang; Xin Bai; Li Chen; Qianyu Peng; Ru Jin; Li Mao; Xiuli Li; Zhengyu Jin; et al. (Insights into Imaging, 2023)
Key points The U-Net model showed a good performance for prostate zonal segmentation. The U-Net model outperformed the junior radiologist in peripheral zone segmentation. Prostate morphology and MR scanner parameters may affect the model’s performance.